A comparative study on sperm penetration in estrual mucus and polyacrylamide gel in relation to seminal characteristics - KAUSHAL, GAGANDEEP; PANGAONKAR, G R; VERMA, H K (The Indian Journal of Animal Reproduction, 2023)
l!J. vitro sperm mucus penetration study was done in freshly collected estrual mucus of buffaloes and in synthetic migration media i.e. polyacrylamide gel (2%). Sperm mucus penetration distance was measured as an indicator of fertility . Sperm mucus penetration distance values have +ve correlation with live and normal sperm count. In polyacrylamide there was +ve correlation between sperm penetration distance value and normal sperm count. Polyacrylamide gel can be used successfully as a better substitute penetration media for sperm penetration for assessing the fertility of the semen.